(untitled) (Al-Academy, 2026)
This research to design innovative textiles with artificial intelligence inspired by traditional women’s encoding techniques for his tribe" Banny Malki", and to use this artificial and innovative graffiti with artificial intelligence. the importance of preserving the heritage and the decorative elements of national identity that it holds by taking advantage of and drawing inspiration from Saudi Arabia’s artistic heritage by taking advantage of artificial intelligence in the design of textiles in a contemporary manner. The applied descriptive approach was followed to describe, analyses and employing pottery in innovative textiles through designs artificial-intelligence and their presentation to competent arbitrators for evaluation of innovation in design, relevance to the source of inspiration and feasibility of its application. One of the most important recommendations is to find new entry points for the study of Saudi heritage and to make use of it in the design textiles.